Pendampingan Menulis Penelitian Tindakan Kelas di Larantuka, Flores Timur - Ezra Tari; Lanny I.D. Koroh; Umar Ali; Martin Ch. Liufeto; Talita Tlonaen (Sekolah Tinggi Teologi Real Batam, 2021)
Classroom action training was agreed upon by the service team, starting with concerns about the teacher's difficulties. The service team found that many teachers had not been able to combine observations in class. This research is a way of teacher research in the classroom to find problems in the learning process. The teacher found many problems related to learning, namely process design, media, learning techniques, and learning outcomes. To realize good classroom action research techniques, training is done. Some teachers have not been able to write a good scientific paper. So the service team trains skilled teachers in writing. The method of service in this service begins with planning the location of the service. The plan is carefully prepared to avoid obstacles in the field. This training produces groups of writer teachers according to their respective fields. The team already found teachers who did classroom action research. However, the difficulty in pouring it in the article. So that the team assists in writing classroom action research articles that will be published in journals, follow-up assistance is carried out in WhatsApp groups.Keywords: report; theory; learning; writing; class action AbstrakPelatihan tindakan kelas disepakati oleh tim pengabdian, diawali keresahan akan kesulitan guru dalam melakukannya. Tim pengabdian menemukan masih banyak guru yang belum bisa meramu hasil pengamatan dalam kelas. Kegiatan ini merupakan cara penelitian guru dalam kelas untuk menemukan masalah dalam proses pembelajaran. Guru menemukan banyak masalah terkait pembelajaran, yakni: rancangan proses, media, teknik pembelajaran, dan hasil pembelajaran. Untuk merealisasikan teknik penelitian tindakan kelas yang baik, maka dibuat pelatihan. Ada juga guru yang belum mampu menulis sebuah karya ilmiah yang baik. Maka tim pengabdian melatih guru terampil dalam menulis. Metode pengabdian ini diawali dengan merencanakan lokasi pengabdian. Rencana dipersiapkan dengan matang agar tidak ada kendala di lapangan. Pelatihan ini menghasilkan kelompok guru penulis sesuai bidang masing-masing. Tim menemukan sudah ada guru yang dapat membuat penelitian tindakan kelasn namun masih kesulitan dalam menuangkannya ke dalam artikel sehingga tim mendampingi dalam penulisan artikel penelitian tindakan kelas yang akan diterbitkan di jurnal. Selanjutnya, pendampingan lanjutan dilakukan dalam grup WhatsApp.Kata kunci: laporan; materi; pembelajaran; penulisan; tindakan kelas